Phylogenetic Status of Two Undescribed Zygomycete Species from Korea: Actinomucor elegans and Mucor minutus - Nguyen, Thuong T. T. (Mycobiology, 2017)
During a survey of fungal diversity of the order Mucorales, three zygomycete isolates, CNUFC-YR113-1, CNUFC-KNU16-7, and CNUFC-BS1-1 were isolated from freshwater and soil samples in Korea. The strains were analyzed both morphologically and phylogenetically based on internal transcribed spacer and 28S rDNA gene sequences. Based on their morphology and phylogeny, the CNUFC-YR113-1 and CNUFC-KNU16-7 isolates were identified as Actinomucor elegans, and CNUFC-BS1-1 was identified as Mucor minutus. To the best of our knowledge, the species A. elegans and M. minutus, belonging to an undiscovered taxon, have not been previously described in Korea.